Effect of a supportive training program on anxiety in children with chronic kidney problems and their mothers' caregiver Burden - Niloofar Bahrami; Saeid Pahlavanzadeh; Maryam Marofi (Wolters Kluwer Medknow Publications, 2019)
Background: Chronic problems have a long course of treatment and are one of the important causes of the childhood hospitalization. The aim of this study was to determine the effect of a supportive training program on the children's anxiety and their mothers' caregiver burden. Materials and Methods: This study was a randomized controlled clinical trial, performed on two groups in three stages in the autumn of 2017 on 112 individuals. The study population consisted of all children with chronic kidney problems who hospitalized in Emam Hossein Hospital (Isfahan, Iran) and their mothers. Sampling selection method was convenient. Participants were randomly assigned to experimental (n = 56) and control (n = 56) groups and the supportive training program, that was a self-regulating program, was done for the experimental group. The Face Anxiety Scale and the Zarit Caregiver Burden Scale were completed by both groups before, after and 1 month after the intervention. Statistical significance was set at 5%. Results: There was a significant difference in the mean scores of anxiety and caregiver burden in the experimental group preintervention [anxiety: (t54= 0.31, p = 0.75); caregiver burden: (t54= 1.34, p = 0.18)], postintervention [anxiety: (t54= 5.30, p < 0.001); caregiver burden: (t54= 2.72, p = 0.009)], and follow-up [anxiety: (t54= 2.39, p = 0.01); caregiver burden: (t54= 3.06, p = 0.003)], whereas there was no significant difference in the mean scores of anxiety and caregiver burden in the control group. In order to controlling for pretest scores, the repeated measure analysis of covariance was adopted. Conclusions: The results showed that the supportive training program can reduce children's anxiety and their mothers' caregiver burden and suggesting to nurses, an effective program to reduce the negative effects of hospitalization on children and their mothers.